Analisis Filogeni Thiaridae (Mollusca: Gastropoda) Papua Menggunakan Karakter Morfologi - Suriani Br. Surbakti (Jurnal Biologi Papua, 2012)
The characteristics  morphology and variations of shell can be used to reconstruct the sequence and phylogenetic of Thiaridae. 34 characters and 2 outgroups of Bellamya sp. from Papua and Sulawesi were used to observe 27 species Thiaridae. Phylogenetic Analysis Using Parsimony (PAUP Software Version 4.0., Swofford) and the neighbour joining cladogram were used to reconstruct the phylogenetic relationship and to group the taxa of Thiaridae based on distribution areas of genera separately. The study indicated that  the taxon of Thiaridae can be groupped into 3 clades. Each clade depicts the taxon population based on their distribution areas in Batanta Island, Sorong, Manokwari, and Bintuni Gulf. All molded into one clade. Biak, Supiori, Serui, Wamena, Merauke, and Jayapura are formed one clade. Thiara, Terebia, and Melanoides are genera which formed a clade each genus. While Stenomelania molded into 3 clades. Morphology character and closed regionsof distribution tended to form ingroup clade and sister species.Key words: characters, phylogeni, Thiaridae, dan Papua.